2013
DOI: 10.3892/ijmm.2013.1583
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prehypertension treatment with losartan effectively prevents brain damage and stroke in stroke-prone spontaneously hypertensive rats

Abstract: Prehypertension has been associated with adverse cerebrovascular events and brain damage. The aims of this study were to investigate i) whether short- and long-term treatments with losartan or amlodipine for prehypertension were able to prevent blood pressure (BP)-linked brain damage, and ii) whether there is a difference in the effectiveness of treatment with losartan and amlodipine in protecting BP-linked brain damage. In the present study, prehypertensive treatment with losartan and amlodipine (6 and 16 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…2b), and no difference between males and females. They are clearly different to the hypertensive SHRSP model rats at the same ages [25]. Varied expression of ATP11B immunogold labelling in neighbouring wildtype ECs in the same transverse section of a blood vessel.…”
Section: The Atp11bko Rat Is Normotensivementioning
confidence: 75%
“…2b), and no difference between males and females. They are clearly different to the hypertensive SHRSP model rats at the same ages [25]. Varied expression of ATP11B immunogold labelling in neighbouring wildtype ECs in the same transverse section of a blood vessel.…”
Section: The Atp11bko Rat Is Normotensivementioning
confidence: 75%
“…After stimulation of LI11, ST36, HT7, and LI15 for 30 min in SHRs, the plasma Ang II levels in the LI11, ST36, and HT7 groups and the aldosterone (ALD) levels in the ST36 and HT7 groups were lowered significantly, and the plasma atrial natriuretic peptide (ANP) content in the HT7 group increased obviously [88]. Inhibition of the renin-angiotensin-ALD system (RAAS) is associated with reduced stroke-induced brain damage [89], and ANP protects against cardiac remodeling [90]. …”
Section: The Potential Of Acupuncture For Secondary Prevention Of Strmentioning
confidence: 99%
“…The study found that the incidence of cardiovascular events in the people with prehypertension in the future was two times as that of the people with normal blood pressure [ 8 ]. It is also proved that stress-induced hypertension is preceded by the damage of target organs like blood vessels [ 9 ], heart [ 10 ], brain [ 11 ], and kidneys [ 12 ] and changes of the expressions of relative proteins and genes. Therefore, early stage treatment could effectively reduce the incidence of high blood pressure and protect target organs.…”
Section: Introductionmentioning
confidence: 99%